2020
DOI: 10.1038/s41598-020-65475-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electron Correlation on Describing QM/MM Interactions in the Attendant Molecular Dynamics Simulations of CO in Myoglobin

Abstract: well by the QM/MM method using the electrostatic embedding approach 16. This is as expected, because most of the protein functions are primarily achieved by the electrostatic 17-21. For example, as previous works demonstrate, the electric field that a protease exerts at the active site is one of the most important origins of its catalytic power 22-26. With the advances in computer hardware and computational methods 27-31 , a number of QM/MM molecular dynamics (MD) studies employing various implementations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Similar to the EEC-QF model, previous studies have shown that ESP-derived charges for a chemical bond exhibit a linear relationship with the electric field along the bond . Therefore, it is expected that the predicted EIs of ESP-derived charges will follow a quadratic function relationship with different environments (or electric fields).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar to the EEC-QF model, previous studies have shown that ESP-derived charges for a chemical bond exhibit a linear relationship with the electric field along the bond . Therefore, it is expected that the predicted EIs of ESP-derived charges will follow a quadratic function relationship with different environments (or electric fields).…”
Section: Resultsmentioning
confidence: 85%
“…Similar to the EEC-QF model, previous studies have shown that ESP-derived charges for a chemical bond exhibit a linear relationship with the electric field along the bond. 121 Therefore, it is expected that the predicted EIs of ESP-derived charges will follow a quadratic function relationship with different environments (or electric fields). The relationship between the ESP-derived charges and the electric field for the O−H bond is depicted in Figure 4C, with the best-fit line given by the equation q H ESP =0.00052805|E ⃗ OH | + 0.39882 (the units of q H ESP and |E ⃗ OH | were in e and MV/cm, respectively).…”
Section: Underlying Reasons For the Disparities Between The Eec And T...mentioning
confidence: 99%
“…Among them, heme proteins, the family of proteins containing an iron–porphyrin complex as a prosthetic group, were widely studied using QM/MM methodologies, especially in order to obtain information on ligand binding ,, and catalysis. ,, Particularly the globin family is one of the most studied, including the well-known mammalian hemoglobin and myoglobin, widely used as reference systems for both computational and experimental method developments. Globins are able to bind (and perform reactions) with small ligands such as O 2 , NO, and CO, as well as other reactive oxygen and nitrogen species (RNOS), and given the extensive structural and spectroscopic available data in a wide variety of conformational and ligand bound states, such as the paradigmatic CO bound myoglobin, they have been extensively studied using QM/MM strategies. , …”
Section: Selected Examplesmentioning
confidence: 99%
“…The binding of carbon monoxide (CO), and more in general of small molecules, to the sixth coordination site of iron­(II) in the heme prosthetic group of myoglobin (both horse-heart and sperm-whale) has received a great deal of attention from basic research. A huge number of fundamental studies, focused on a large variety of structural, spectroscopic, thermodynamic, and kinetic aspects has been indeed devoted to carboxymyoglobin (MbCO) and oxymyoglobin (MbO2), as well as their mutants, both experimentally and computationally. In this context, the stationary and time-dependent infrared (IR) spectral behavior of the heme-bound CO stretching frequencies was particularly interesting , i.e., both the behavior associated with the Fe–C mode (hereafter ν Fe–C ) and the one associated with C–O mode (hereafter ν CO ), whose spectral signal interpretation turned out to be crucial for understanding the mechanisms underlying the binding differences between CO and O 2 to iron­(II). Specifically, the IR signal of ν CO in MbCO is characterized by three different substates, denoted as A 0 (≃1965 cm –1 ), A 1 (≃1945 cm –1 ), and A 3 (≃1934 cm –1 ), also showing other relevant features such as different CO rebinding rates, different dephasing rates, and different sensitivities to pH . A fourth substate, usually indicated as A x , appears as scarcely relevant in physiological conditions.…”
Section: Introductionmentioning
confidence: 99%